The effect of telenursing on the self-efficacy of covid-19 patients after discharge from hospital - Ahmad Rajab Dizavandi; Abolfazl Shakiba; Sedigheh Rastaghi; Mostafa Rad (Mashhad University of Medical Sciences, 2021)
Background: Considering the complications of covid-19, in order to improve the quality of the care services and ensure of the continuity of these care services out of the hospital, telenursing should be taken.Aim: This study aimed to evaluate the effect of telenursing on the self-efficacy of the covid-19 patients after discharge from hospital.Method:  This clinical trial was conducted on 66 covid-19 patients in sabzevar vasei hospital, Iran, during 2021. This participants have been divided to intervention and control groups with permutation blocks of random allocation method. Data collection tools included the demographic questionnaire and the covid-19 Prevention, Recognition, home-management self-efficacy scale were completed online by the participants before and one month after the intervention. A workshop through multimedia app and telenursing was performed to educate patient in the intervention group for one month. The control group only received the usual care at discharge. Finally, the data were analyzed using SPSS software (version 24) through the independent t-test, paired t-test, Chi-square test, and Fisher's exact test.Results: In the control group, the average scores of self-efficacy before and after routine training were 165.66 ±15 and 159.69± 21 21.73, respectively, and in the experimental group before and after telenursing were 144.24± 20.58 and 172.15±13.28, which was significant difference between results (p <0.001).Implications for practice: It seems that telenursing was effective on self-efficacy of patients. Accordingly, nursing team are recommended to use telenursing to improve the self-efficacy of the covid-19 patients.